Investigation of Possible Oxidative Damage Caused by Formaldehyde Exposure in the Rat's Heart and Aorta Tissue - Tasdemir,Rabia (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Formaldehyde (FA) is a toxic substance used frequently in the field of medicine as well as in many industrial areas. Especially people working in the field of anatomy, histology, and pathology are in high risk group because of the use of the FA. Studies showing the effects of FA on the cardiovascular system are few in number. The purpose of the present study was to investigate the effects of FA exposure, which we believe can cause oxidative stress, on the heart and aorta with various biochemical analyses. A total of 24 Wistar Albino rats were used in our study. We divided the rats into 3 groups as the Control Group (CG), the group exposed to low-dose FA (avg. 1 ppm) (DDG) Group, and the group exposed to high-dose FA (avg. 10 ppm) (YDG). At the end of the subchronic FA exposure, the blood samples, heart and aorta tissues of the rats were taken and subjected to biochemical analyses. As a result of the analyses, statistically significant differences were detected between CG (2.96?0.85 ng/mg), and HDG (2.08?0.77 ng/mg) in aortic tissues in TXNIP analysis (p<0.05). In heart tissues, significant differences were detected between CG (0.73?0.27 ng/mg) and LDG (1.13?0.22 ng/mg) (p<0.05). Statistically significant differences were also detected between CG (1.98?0.31 mM/ml) and YDG (2.43?0.31 mM/ml) in serum MDA analyses (p<0.05). It was shown that subchronic application of FA to LDG rats through inhalation had no effects on apoptosis markers in heart tissues. More studies are required to show FA toxicity and the mechanism of action of pathology on the cardiovascular system. We believe that our study will contribute to clarifying the roles of mild and subchronic exposure of FA in heart and aortic tissues in terms of oxidative stress risk.